PENGARUH SISTEM OLAH TANAH DAN PEMBERIAN MULSA BAGAS TERHADAP POPULASI FUNGI MIKORIZA ARBUSKULA PADA PERKEBUNAN TEBU - Listyowati, Mastutik Sri; Yusnaini, Sri; Rini, Maria Viva; Arif, M. A. Syamsul (JURNAL AGROTROPIKA, 2013)
Intensive soil tillage in sugarcane plantation may cause soil degradation including soil microorganism activities. The experiment was conducted at PT GMP to test the effect of soil tillage systems and bagasse application on arbuscular mycorrhiza fungi (AMF) population. The experimental design used was a completely randomized design arranged in a split plot with five replications. The main plot consisted of intensive soil tillage and no tillage system. The sub-plot consisted of 80 ton ha-1 bagasse application, and without bagasse application. The result showed that AMF population in intensive soil tillage was not signicantly different over no tillage system. AMF population in the soil applied with 80 t ha-1 bagasse was also not signicantly different over no bagasse. There was no interaction between soil tillage systems and bagasse application on arbuscular mycorrhiza fungi (AMF) population.  Key words: arbuscular mycorrhiza, population, sugarcane, soil tillage, bagasse